2012
DOI: 10.4236/health.2012.411166
|View full text |Cite
|
Sign up to set email alerts
|

Identifying households with low immunisation completion in Bangladesh

Abstract: The objective of this study was to investigate if the mothers' demographics and household characteristics-including type of use of cooking fuel, energy and toilet facilities-have any implication for complete immunisation rates among their children. A cross-sectional data analysis of a nationally representative sample of 4925 women with at least one child was performed. Chi-squared tests and multivariate logistic regression analyses were used. Immunisation coverage was positively associated with the mother's ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Mothers attended ANC three or above times were around four times [AOR=3.8 (2.1-6.9)] more likely to fully vaccinate their children than mothers attended two or less. This is consistence with study done in Ambo and Bangladesh [10,23]. The reason might be, Mothers who repeatedly attend ANC gets more information related to vaccination and the information they get during their repeated ANC follow up might help them to develop good attitude towards vaccination of children's, which leads them to fully vaccinate their children.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Mothers attended ANC three or above times were around four times [AOR=3.8 (2.1-6.9)] more likely to fully vaccinate their children than mothers attended two or less. This is consistence with study done in Ambo and Bangladesh [10,23]. The reason might be, Mothers who repeatedly attend ANC gets more information related to vaccination and the information they get during their repeated ANC follow up might help them to develop good attitude towards vaccination of children's, which leads them to fully vaccinate their children.…”
Section: Discussionsupporting
confidence: 74%
“…This study also identifies that, mothers received three or above doses of TT vaccine were four times [AOR=4.0 (1.7-9.6)] more likely to fully vaccinate their children than mothers received two or less doses of TT vaccine and the finding is also consistence with study done in Ambo and Bangladesh [10,23]. This might be explained by; mothers who got three and more dose of TT might have better knowledge and attitude on vaccination and have good commitment to getting vaccinated their child based on the schedule.…”
Section: Yes (%) No (%)supporting
confidence: 81%
See 1 more Smart Citation
“…One study conducted in urban setting of Dhaka, Bangladesh found 83% children fully vaccinated like our study (15,16) . Demographic and health survey (DHS) of Bangladesh performed in a sample of 4925 parents having at least one child, concluded that there was massive gap in vaccination in rural-urban context of Bangladesh (17) . In this scenario, our study is closer to the findings of Pakistan demographic and health survey (PDHS) 2012-13 where 66% children of urban areas and 48% children of rural areas were found fully vaccinated (18) .…”
Section: Sample Characteristics and Vaccination Statusmentioning
confidence: 99%
“…[5][6][7] The latest data from the United States of America (USA) have revealed an increase in alternative vaccination programs in addition to vaccination for preschool children. 3,4 Vaccine hesitancy is not a new occurrence, its negative impact on preventive services is gradually increasing. It has been shown that rejection or hesitation of vaccinations are associated with higher socioeconomic status,…”
mentioning
confidence: 99%